THE ROLE OF STRATEGIC AUDITING IN ACHIEVING SUSTAINABLE PERFORMANCE AND ITS IMPACT ON IMPROVING THE COMPETITIVE ADVANTAGE OF THE PRODUCT (A PRACTICAL STUDY IN SOME ORGANIZATIONS REGISTERED IN THE IRAQ STOCK EXCHANGE) (World Bulletin of Management and Law, 2023)
The research aims to identify the conceptual framework of strategic auditing, competitive advantage and the four dimensions of sustainable performance (the economic dimension, the social dimension, the ethical dimension, the environmental dimension), and to identify and analyze the relationship (correlation and impact) between strategic auditing in achieving sustainable performance and improving the competitive advantage of the product. Use The researcher uses the deductive method based on statistical measurement tools in scientific research by preparing a questionnaire to find out the opinions of a sample of employees in organizations. (55) Questionnaire forms were distributed to the aforementioned sample, (52) forms were retrieved from them to conduct statistical analysis and identify the results. The researchers reached a set of conclusions, the most important of which is the strategic audit function, in its approved manner in organizations, no longer meets work requirements and satisfies shareholders and stakeholders. Among the recommendations, the most important of which is the need for the research sample organizations to provide a set of skills that are aware of the requirements of the assigned tasks and achieve sustainable performance in order to continue in the competition market, to enhance the technical and professional aspects, to develop and activate programs and training courses for the employees of the organization on an ongoing basis, and to participate in various activities.